1978
DOI: 10.1038/bjc.1978.194
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid tumours in rats and hepatomas in mice after griseofulvin treatment

Abstract: Summary.-Griseofulvin, an antibiotic used to treat dermatophytosis, was tested for carcinogenicity in mice, rats and hamsters. Three groups of mice and rats were given the drug in powdered diet in alternating 5-week periods for life, at dose levels of 3.000, 1-500 and 0-300 (mice) and 2.0%, 1-0% and 0-2% (rats). A group of mice and 3 groups of hamsters received continuous daily treatment for life with griseofulvin at 3-000, 1.5%, 0.300 and 0.1% dose levels respectively. A significant incidence of hepatic tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The mechanism is unclear since it does not disrupt microtubules like some other spindle poisons but it does appear to bind to tubulin or at least to microtubule-associated proteins (Grisham et al, 1973;Wehland et al, 1977;Ueno, 1985;De Carli & Larizza, 1988). Moreover, studies in mice demonstrated that griseofulvin was hepatocarcinogenic in mice after oral dosing and it resulted in thyroid tumours in rats (Rustia & Shubik, 1978). Dietary administration to mice resulted in hepatotoxicity, disruption of hepatic architecture and lesions which had the appearance of liver tumours (De Matteis et al, 1966).…”
Section: Griseofulvinmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism is unclear since it does not disrupt microtubules like some other spindle poisons but it does appear to bind to tubulin or at least to microtubule-associated proteins (Grisham et al, 1973;Wehland et al, 1977;Ueno, 1985;De Carli & Larizza, 1988). Moreover, studies in mice demonstrated that griseofulvin was hepatocarcinogenic in mice after oral dosing and it resulted in thyroid tumours in rats (Rustia & Shubik, 1978). Dietary administration to mice resulted in hepatotoxicity, disruption of hepatic architecture and lesions which had the appearance of liver tumours (De Matteis et al, 1966).…”
Section: Griseofulvinmentioning
confidence: 99%
“…Moreover, studies in mice demonstrated that griseofulvin was hepatocarcinogenic in mice after oral dosing and it resulted in thyroid tumours in rats (Rustia & Shubik, 1978). Dietary administration to mice resulted in hepatotoxicity, disruption of hepatic architecture and lesions which had the appearance of liver tumours (De Matteis et al.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the prolonged oral administration of GF disturbs hepatic porphyrin metabolism, and induces liver damage and increased hepatic tumor incidence [5][6][7][8]. In another study long-term feeding of GF (0.2% to 2% in the diet) led to thyroid adenomas and carcinomas, but the limited studies available do not indicate definitely whether the compound is a hepatocarcinogen in this species [9]. Barich et al [10] showed that GF promoted skin tumor development in mice when given orally after methylcholanthrene initiation, but no published studies on the tumor promoting potential of GF in the liver are available.…”
Section: Introductionmentioning
confidence: 99%
“…Induction o f hepatomas by G F was also reported after administration o f milligram quantities to infant mice [11]. Dietary ex posure to G F produced a significant incidence o f hepa tocellular tumors in mice, thyroid tumors in rats, but no carcinogenic activity in hamsters [12]. G F may also act either as a promoting or a carcinogenic agent, depending on the circumstances o f its administration [4], A cocarcinogenic effect on skin tumor development in mice was noted when G F was administered orally before, during or after topical treatment with methylcholanthrene [13][14][15].…”
Section: Introductionmentioning
confidence: 76%